2020
DOI: 10.1038/s41598-020-61427-y
|View full text |Cite|
|
Sign up to set email alerts
|

Mutually exclusive locales for N-linked glycans and disorder in human glycoproteins

Abstract: Several post-translational protein modifications lie predominantly within regions of disorder: the biased localization has been proposed to expand the binding versatility of disordered regions. However, investigating a representative dataset of 500 human N-glycoproteins, we observed the sites of n-linked glycosylations or n-glycosites, to be predominantly present in the regions of predicted order. When compared with disordered stretches, ordered regions were not found to be enriched for asparagines, serines an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 57 publications
3
3
0
Order By: Relevance
“…Analysis of ordered and disordered localization of the Nglycosite using ODiNPred showed that at position N37, the probability of the N-glycosite to be located in a disordered region was 0.0342 (Figure 4D). All N37 neighbouring amino acid residues had low probabilities of disorder, in agreement with findings on N-glycosites of human proteins [94]. (Q86SR1/ GALNT10) at positions N124, N146 and N593 [95], glycosites also conserved in M. mulatta GALNT10.…”
Section: Supplementary Figure 4 Gene Ontology Analysis Of Llc-mk2 Deglycoproteome Following Lda Top 20 Genesupporting
confidence: 87%
“…Analysis of ordered and disordered localization of the Nglycosite using ODiNPred showed that at position N37, the probability of the N-glycosite to be located in a disordered region was 0.0342 (Figure 4D). All N37 neighbouring amino acid residues had low probabilities of disorder, in agreement with findings on N-glycosites of human proteins [94]. (Q86SR1/ GALNT10) at positions N124, N146 and N593 [95], glycosites also conserved in M. mulatta GALNT10.…”
Section: Supplementary Figure 4 Gene Ontology Analysis Of Llc-mk2 Deglycoproteome Following Lda Top 20 Genesupporting
confidence: 87%
“…Analysis of ordered and disordered localization of the Nglycosite using ODiNPred showed that at position N37, the probability of the N-glycosite to be located in a disordered region was 0.0342 (Figure 4D). All N37 neighbouring amino acid residues had low probabilities of disorder, in agreement with findings on N-glycosites of human proteins [94]. Two of the proteins identified in subset iii) included proteins involved in the protein glycosylation machinery; hexosyltransferase (F6UCJ0/ B3GALNT1) and polypeptide Nacetylgalactosaminyltransferase (A0A1D5QY41/GALNT10).…”
Section: Deglycoproteome Analysis By Pca and Euclidean Distance Showe...supporting
confidence: 84%
“…Thermodynamic and experimental analyses have shown that N-glycosylation often stabilize the glycoprotein structure [109,110]. N-glycosites are found mainly in ordered regions; amino acid residues surrounding Nsequons are relatively poor in hydrophobic and bulky residues known to promote disordered regions [94]. Proteome-wide structural analysis of N-glycosites from human, mouse, fly, plant and yeast showed that a high proportion of N-glycosites are localized within a turn/loop and are solventexposed [111][112][113].…”
Section: Deglycoproteome Analysis By Pca and Euclidean Distance Showe...mentioning
confidence: 99%
“…Glycoprotein is a combination of protein and carbohydrate. There are different types of glycoproteins, however, the most common glycoproteins that make virus spikes, like the spike of the coronaviruses, are O-Link and N-Link types [39][40][41][42][43]. If the causative of carbohydrate-binding to protein is oxygen atoms, it is called O-Link, and if it is nitrogen atoms, it is called N-Link.…”
Section: Resultsmentioning
confidence: 99%